Milly and Molly help the animals - Pittar, Gill; Morrell, Cris (MM House Pub. Gisborne, N.Z., 2003)
Milly and Molly stand up for animal rights when developers threaten to destroy the habitat of the local animals. Includes teaching guide. Suggested level: junior